THE EFFECT OF FINGER GRIP THERAPY ON BLOOD PRESSURE CHANGES IN HYPERTENSION PATIENTS AT IMELDA HOSPITAL INDONESIA WORKERS (IPI) MEDAN - Nova Linda Rambe; Rahmawani Fauza Fauza; Eva Nirwana Hutabarat; Eswinel Hasibuan (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Hypertension is an increase in high blood pressure above normal. Finger grip relaxation is a simple relaxation technique with the touch of a hand which involves breathing to balance the energy in the body, so as to be able to control emotions which will make the body relax. This study aims to determine the effect of finger grip therapy on changes in blood pressure in hypertensive patients at the Indonesian Workers' Imelda Hospital This study uses quantitative research methods with Quasy experimental design with the Pre Test-Post Test One Group approach. The number of respondents in this study were 30 respondents who were taken by accidental sampling. The instrument used is an observation sheet to find out how blood pressure changes before and after being given therapy. The intervention was in the form of an independent act of holding fingers for 3-5 minutes. The research tool used was a sphygnomanometer to measure blood pressure. The results of the analysis with the Wilcoxom test obtained a p-value of 0.000 (p <0.05) on systolic and diastolic blood pressure, so that there was an effect of finger grip therapy on blood pressure in hypertension sufferers at the Indonesian Workers' Imelda Hospital (IPI) Medan.